2017
DOI: 10.1038/nrendo.2017.56
|View full text |Cite
|
Sign up to set email alerts
|

Hepatokines: linking nonalcoholic fatty liver disease and insulin resistance

Abstract: Hepatic steatosis is an underlying feature of nonalcoholic fatty liver disease (NAFLD), which is the most common form of liver disease and is present in up to ∼70% of individuals who are overweight. NAFLD is also associated with hypertriglyceridaemia and low levels of HDL, glucose intolerance, insulin resistance and type 2 diabetes mellitus. Hepatic steatosis is a strong predictor of the development of insulin resistance and often precedes the onset of other known mediators of insulin resistance. This sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
428
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(455 citation statements)
references
References 189 publications
14
428
1
12
Order By: Relevance
“…These diseases that are associated with NAFLD may increase the risk of cardiovascular disease and further aggravate the liver damage [68]. Therefore, the key to the treatment of NAFLD is the improvement of the metabolic disturbances associated with insulin resistance [69]. Insulin-sensitizing drugs, such as metformin, may correct some of these metabolic disorders [70].…”
Section: Discussionmentioning
confidence: 99%
“…These diseases that are associated with NAFLD may increase the risk of cardiovascular disease and further aggravate the liver damage [68]. Therefore, the key to the treatment of NAFLD is the improvement of the metabolic disturbances associated with insulin resistance [69]. Insulin-sensitizing drugs, such as metformin, may correct some of these metabolic disorders [70].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the liver participates in metabolic regulation, through the expression and secretion of organokines, which are also referred to as hepatokines. Interestingly, these proteins influence metabolic processes through paracrine and endocrine signaling, rather than by autocrine signaling (17). Hepatokines include several growth factors such as fibroblast growth factor 21 (18), insulin-like growth factors, angiopoietin-related growth factor, and HGF.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has suggested that hepatokines, such as Fetuin-A, retinol-binding protein 4, sex hormone-binding globulin and adropin, play as important roles in the link of NAFLD to insulin resistance [36]. Fetuin-B, as one of the novel hepatokines that induced metabolic dysregulation, was also found to be associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 95%